Rapid Micropropagation of Alocasia azlanii using Microshoot Tips as Explants Source - Siregar, Ahmad Syahrian; Mas’udah, Shofiyatul; Firdiana, Elok Rifqi; Widiarsih, Sasanti; Budiarto, Kurniawan; Yusuf, Hadi Mokhamad; Yulianah, Izmi; Masnar, Adley L. (AGRIVITA Journal of Agricultural Science, 2025)
Alocasia azlanii is a unique species that has an ornamental value, native to Southeast Asia. The present investigation aimed to develop reliable in vitro propagation techniques for A. azlanii, suitable for potential mutation and polyploidization programs. The in vitro propagation protocol for these species includes sterilization, shoot proliferation, in vitro rooting induction, and acclimation stages. The results showed that the effective protocol for freeing the explants from contamination was achieved through additional pre-treatment with bactericide and fungicide, which produced the best percentage of clean shoot-tip explants (87%). At the shoot multiplication stage, the shoot-tip explant cultivated in MS medium supplemented with 0.05 mg/l TDZ and 1 mg/l BAP showed the highest number of shoots (31.8) in the second subculture cycle. In rooting stages, single shoots that were planted in MS medium supplemented with 0.5 mg/l activated charcoal and 0.5 mg/l NAA resulted in the best plantlet performances in terms of stem diameter, number of roots, number of leaves, and plantlet height. In the acclimatization stage, planting media composed of husk charcoal, soil, manure, and volcanic fine sand mixture (2:1:1:1 v/v) preserved vigorous plantlet development, with 93% survival.